E-131 Outcomes of mechanical thrombectomy for acute ischemic stroke in native american population: a preliminary study. (22nd July 2019) - Ikram, A; Suriya, S; Farooqui, M; Owens, O; Alvarado Arias, A; Sorte, D; Carlson, A; Ortega-Guiterrez, S; Torbey, M; Zafar, A
Abstract : Objectives: The primary objective of this study is to evaluate the difference in the functional and neurological outcomes after mechanical thrombectomy (MT) for an acute ischemic stroke (AIS), between Native Americans (NA) patients versus other ethnicities. Background: There is scarcity of data regarding outcome of MT in NA population. Considering the dynamics of the state of New Mexico and a diverse patient population, we evaluated the difference in outcome between NA patients with comparison group representing other ethnicities. Methods: This is a preliminary, observational retrospective case-control study. All NA patients who underwent MT for LVO from January 01, 2016 to December 31, 2018 at UNMH were included. Data was extracted from Cerner database at UNMH and was collected on secured Redcap™ database. Patients were categorized into NA vs comparison group (other ethnicities) into two groups, with the ratio of 1:4 respectively. Results: A total of 35 patients who underwent MT at UNMH for an AIS were included in analysis: seven NA and 28 controls. Nine patients (NA=7) were directly admitted through ED while 26 were transferred from outside hospitals (NA=6). Prevalence of vascular risk factors, including Hypertension, hyperlipidemia, Coronary artery disease, Diabetes Mellitus was noticeably higher in NA than the comparison group. There was no statistical difference in the two groups with regards to median time interval from last known well (LKW) to groin puncture, and from LKW to reperfusion. The mortality was 14% in NA group and 4% in the comparison group. The median NIHSS on discharge between NA and comparison group was 13 and 15.5, respectively. The median mRS at 6 months follow up was 1 in NA and 2 in comparison group, however this was not statistically significant. Conclusion: This is the first ever descriptive study evaluating outcomes in NA patients undergoing MT. Prevalence of vascular risk factors in NA was noticeably higher compared to the comparison group. Our retrospective study showed that Native American patients similar functional and neurological outcomes for thrombectomy. Disclosures: A. Ikram: None. S. Suriya: None. M. Farooqui: None. O. Owens: None. A. Alvarado Arias: None. D. Sorte: None. A. Carlson: None. S. Ortega-Guiterrez: None. M. Torbey: None. A. Zafar: None.